Body Mass Index as a Patient Selection Criterion for Kidney Transplant - Urbanski, Megan; Inaganti, Salini; Agu, Chidera; Sarwer, David; Gardiner, Heather (CommonHealth, 2020)
There is currently no consensus on the ideal body mass index (BMI) for kidney transplantation, yet an elevated BMI can limit access to transplantation. This study explored the attitudes of kidney transplant professionals regarding BMI as a selection criterion for kidney transplantation. Brief, in-person interviews were conducted at the 2016 American Transplant Congress. Participants were queried on their views regarding kidney transplant eligibility for patients with classes 1, 2, and 3 obesity, as well as their transplant centers’ BMI-related policies. Most (88%) of the 94 participants did not consider class 1 obesity (BMI 30 to < 35) a contraindication to kidney transplantation, with a greater number of participants reluctant to consider patients with class 2 (BMI 35 to < 40) or class 3 obesity (BMI ³ 40) for transplantation. Participants identified a mean maximum BMI 2.3 points higher than the mean maximum BMI reported in transplant center patient selection criteria policies. Overall, kidney transplant professionals viewed BMI as a useful patient selection criterion when considered within the larger context of the patient’s clinical picture. Future research should assess outcomes for transplant recipients with varying obesity levels.